2018
DOI: 10.1093/rheumatology/key023
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic infections in rheumatoid arthritis patients exposed to biologic therapy: results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis

Abstract: The overall rate of OI was not significantly different between drug classes; however, a subtle difference in the pattern of OI was seen between the cohorts. Patient factors such as age, gender and comorbidity were the most important predictors of OI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 13 publications
2
66
1
4
Order By: Relevance
“…In the BSRBR-RA registry (British Society for Rheumatology Biologics Register of RA patients), incidence of OI was 1.34/1000 pyrs. 46 A similar incidence (though across all indications for TNF inhibitors) was reported in French Registry of Infections and Lymphoma in Patients Treated With TNF-α Antagonists: 1.52/1000 pyrs. 47 This study also demonstrated a higher odds of OI for patients receiving monoclonal antibody treatment than ETN in the case-control analysis (IFX: OR, 17.6; 95%CI, 4.3-72.9; ADA: OR, 10.28; 95%CI, 2.35-44.94) but with no statistically significant difference in the incidence.…”
Section: Infectionssupporting
confidence: 61%
See 2 more Smart Citations
“…In the BSRBR-RA registry (British Society for Rheumatology Biologics Register of RA patients), incidence of OI was 1.34/1000 pyrs. 46 A similar incidence (though across all indications for TNF inhibitors) was reported in French Registry of Infections and Lymphoma in Patients Treated With TNF-α Antagonists: 1.52/1000 pyrs. 47 This study also demonstrated a higher odds of OI for patients receiving monoclonal antibody treatment than ETN in the case-control analysis (IFX: OR, 17.6; 95%CI, 4.3-72.9; ADA: OR, 10.28; 95%CI, 2.35-44.94) but with no statistically significant difference in the incidence.…”
Section: Infectionssupporting
confidence: 61%
“…Low incidence of OI after TNF inhibitors was calculated also from other biologic registries. In the BSRBR‐RA registry (British Society for Rheumatology Biologics Register of RA patients), incidence of OI was 1.34/1000 pyrs . A similar incidence (though across all indications for TNF inhibitors) was reported in French Registry of Infections and Lymphoma in Patients Treated With TNF‐α Antagonists: 1.52/1000 pyrs .…”
Section: Infectionsmentioning
confidence: 59%
See 1 more Smart Citation
“…TNF-α is a vital cytokine mediating host immune response [227]. Inhibition of TNF leads to a significant decrease of the inflammatory response, and this approach is used in therapy of autoimmune conditions, most effectively in RA, juvenile idiopathic arthritis, PsA, Psoriasis (PsO), Spondyloarthritis (SpA) and inflammatory bowel disease [228].…”
Section: Tumor Necrosis Factor α Inhibitorsmentioning
confidence: 99%
“…Updated data from the British Society for Rheumatology Biologics Register for rheumatoid arthritis showed the incidence rate of opportunistic infections was low at 1.33 cases per 1000 patient years 8. The authors looked at 19 162 patients and included patients who were either on anti-TNF therapy, rituximab or tocilizumab.…”
Section: Discussionmentioning
confidence: 99%